The Total Erythrocyte Count, Hematocrit Value, and Hemoglobin Concentration in Broiler Supplemented With Feed Additive - Aryani Sismin Satyaningtijas; Sus Dherti Widhyari; Ratna Delima Natalia (Jurnal Kedokteran Hewan, 2010)
The aim of this research was to find out the total erythrocyte count, hematocrit value, and hemoglobin concentration in broiler chicken treated with turmeric, garlic, and zinc supplementation. One hundred broiler chickens were divided intofive groups by randomized and four replications of each. Feed supplement combinations were R0 (basal), R1 (garlic and turmeric), R2 (garlic and zinc), R3 (turmeric and zinc), and R4 (turmeric, garlic and zinc). Blood sample was taken at the age of 6 weeks after treatment to determine total erythrocyte count, hematocrit value, and hemoglobin concentration. The result showed that total erythrocyte count in group of R3 (turmeric powder 1.5% and zinc oxide 120 ppm) were significantly higher than R0 (P0.05) were 3.32±0.73x106/ìl. Total erythrocyte count, hematocrit value, and hemoglobin concentration groupof R2 and R3 were tended to be higher than R0, meanwhile group of R4 did not different from R0. Feed supplemented with hebal and zink would increase the total erythrocyte count, hematocrit value, and hemoglobin concentration in broiler chicken.